PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGANI KASUS IMIGRAN DI BENJINA INDONESIA PERIODE 2015 - 2017 - Mutiara Kusuma Sari, - (2018)
This research entitled " The Role of International Organization for Migration (IOM) in Handling Human Trafficking Case in Benjina Indonesia period 2015 - 2017 ". The international community is now faced with global issues related to the " New World Order ". Issues on these welfare issues relate to Human Security between developed countries and environmental issues. In the case of these immigrants revealed the existence of Human Trafficking practices in the form of immigrant labor slavery. The issue of human trafficking has become one of the important conflicts raised in the international security agenda. In 2015, an American press agency (AP) revealed the practice of trafficking of persons in the form of labor slavery in the fishing industry in Benjina Indonesia. The Government of Indonesia with IOM, responded appropriately to cases of human rights violations. The role of international organizations in international relations has been recognized for its success in solving various problems facing a country. IOM is an organization that works to encourage orderly and humane migration practices, and helps find practical solutions to the issue of migration and provides humanitarian assistance to needy groups. The author uses theories and concepts, namely the theory of International Organization, the concept of Human Security, and the concept of human rights. The author uses the International Organization theory to analyze whether the role of IOM in accordance with the roles of the International Organization described in the theory, then the author uses the concept of Human Security and the concept of Human Rights to describe the case of Human Trafficking in Benjina Indonesia which is a threat in Human Security and very violate HAM. The author uses qualitative methods by explaining the case, as well as the collection of primary and secondary data through data analysis and interviews. The results of this study explain that IOM handles the case by providing technical assistance in the form of victim identification, return assistance, food and non-food aid, health assistance, victim reintegration assistance, and legal aid